Chronic Inflammatory Diseases and the Acute Respiratory Distress Syndrome (ARDS) - Fernandez-Bustamante, Ana; E. Repine, John (Current Pharmaceutical Design, 2014)
The Acute Respiratory Distress Syndrome (ARDS) is a highly fatal pro-inflammatory oxidative respiratory disease. Relatively recently, the modulating effects of chronic inflammatory processes on ARDS susceptibility have been recognized in a number of clinical studies. Herein, we briefly review some of the chronic conditions that have been reported to increase (cigarette smoking and alcohol abuse) or decrease (diabetes and obesity) susceptibility to ARDS. We also propose some potential pathways that may hold clues regarding the pathogenesis and/or therapy for ARDS.
Keywords: ARDS